2021
DOI: 10.2147/ijn.s316326
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Terpesomes and Leciplex for the Effective Ocular Conveyance of Moxifloxacin Hydrochloride (Comparative Assessment): In-vitro, Ex-vivo, and In-vivo Evaluation

Abstract: Aim To compare the ability of both terpesomes (TPs) and leciplex (LPs) loaded moxifloxacin hydrochloride (MOX) for enhancing ocular drug conveyance. Methods Two separate 2 1 .3 1 full-factorial trials were established to determine the influence of multiple variables upon nanovesicles properties and select the optimized formulae using Design Expert ® software. The thin-film hydration method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 47 publications
5
17
1
Order By: Relevance
“…Considering the DDAB amount (X 3 ), it was found that by increasing the DDAB amount from 5 to 15 mg the amount of LVC entrapped decreased. The previous findings were in accordance with Albash et al, 2021d as they described upon increasing cationic SAA as DDAB the EE% of leciplex loaded Moxifloxacin hydrochloride decreased. In addition, they correlate the lower EE% values at high DDAB concentration owed to the enhancement of PC solubility by SAA, promoting the drug leak from vesicles.…”
Section: Resultssupporting
confidence: 91%
“…Considering the DDAB amount (X 3 ), it was found that by increasing the DDAB amount from 5 to 15 mg the amount of LVC entrapped decreased. The previous findings were in accordance with Albash et al, 2021d as they described upon increasing cationic SAA as DDAB the EE% of leciplex loaded Moxifloxacin hydrochloride decreased. In addition, they correlate the lower EE% values at high DDAB concentration owed to the enhancement of PC solubility by SAA, promoting the drug leak from vesicles.…”
Section: Resultssupporting
confidence: 91%
“…These results may be due to the solubilization of phospholipid by the cationic SAA, leading to decreasing STZN encapsulation into the LP. Contrary to previous literature that pointed out the positive impact of the double-chain cationic SAA (DDAB) with a higher log p -value (11.8) on the EE% of lipophilic drugs compared to the single chain CTAB with a lower log p -value 8 [ 30 , 31 ], CTAB increased the EE% of STZN compared to DDAB ( p = 0.0084). DDAB is a double-chain SAA that could compete with the positively charged drug STZN for affinity with the negative phospholipid groups; therefore, by increasing the DDAB molar ratio, the amount of STZN entrapped was reduced.…”
Section: Resultscontrasting
confidence: 75%
“…First, appropriate dilution of the sample was performed, and a drop was dried over a carbon-coated copper grid and stained with 2% w/v phosphotungstic acid solution. Subsequently, imaging of the sample was performed using TEM at 80 kV (Albash et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%